Polystyrene Foam-Based Leg Tip Strider Robot - Addie Irawan, Hashim; Ai, Chern Lim (2013)
This paper presents the water strider robot design with polystyrene foam-based leg tip approach. With reference to the biological size and flexible maneuverability of water strider this robot suitable to be applied as autonomous instrumentation unit for water quality monitoring application. The density of the main body is designed with less than 1g/cm3, which is less than density of the water. Four motors are placed at the four side of the robot’s body and driven by two half-bridge drivers via a microcontroller. The system is remotely control via computer unit through 3DR Radio module. According to the analysis on various experiments it shows that the size of polystyrene foam and the degree of copper leg play important role by supporting the robot’s body and the floating of robot on the water surface.